ANALISIS EFEKTIVITAS VIDEO PEMBELAJARAN DALAM MEMBANGUN KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA SD PADA MATA PELAJARAN PPKn - Ananda Pingka Afrija; Kurnia Marifatul Latifah; Ma'rifatul Luthfatun Nida; Arita Marini (Bajang Institute, 2022)
Learning videos are audio-visual media that are commonly used in teaching and learning activities in the 21st century. The purpose of this study was to find out how effective learning videos are applied in elementary schools to build students' character of discipline and responsibility. The methodology used is a qualitative method with a literature study approach. The form of the activity carried out was conducting library research through data collection using the listening technique, participatory observation taken from Google Schoolar with the keywords ``effectiveness of learning videos